Strategi Digital Marketing Pengusaha Kuliner dalam Meningkatkan Penjualan di Masa Pandemi Covid-19 - Destrilia, Intan; Lendra, I Wayan; Saputra, Pindo Riski (Lembaga Penelitian dan Pengabdian kepada Masyarakat of Universitas Islam Negeri Jurai Siwo Lampung, 2022)
The purpose of this study was to describe digital marketing strategies used by cafés and restaurants during Covid-19 pandemic in Metro City – Lampung. The research employed descriptive quantitative approach by analyzing data from interviews and observations toward 10 cafés and restaurants in Metro City. The results of this study reveal that digital marketing used by cafés and restaurants in Metro City was throughout digital platforms such as Gojek and Grab, then advertising was done through social media Instagram. This shows that the use of digital platforms and social media has proven to be effective in increasing sales and maintaining the existence of a business during this COVID-19 pandemic. The results of this study can be used as a reference source for culinary entrepreneurs in various regions so that they can use digital media to maintain sales targets during the COVID-19 pandemic, where people are prohibited from doing direct activities outside the home, hopefully it can help reduce physical interaction and the spread of the virus.